Using Online Applications on Interest to Buy Fast Fashion on Gen-Z in Indonesia - Grade Banirohim; Asep Hermawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the use of online product purchase applications on buying interest fast fashion on G en - Z in Indonesia. The data used in this study is primary data taken from the results of filling out research respondents' questionnaires distributed by researchers online through an online survey media platform. The research sample was selected using the purposive sampling method to obtain a sample of 260 respondents. The data processing technique used in this research is using SEM which is assisted by using lisrel as software from the structural equation model. The results showed that trust can be influenced by perceived value and perceived enjoyment, while attitude is influenced by perceived usefulness and perceived value. Furthermore, trust can affect eWOM and purchase intention, but attitude is not influenced by trust. The results also show that attitude can affect eWOM but does not affect purchase intention, as well as eWOM which does not affect purchase intention. This research is expected to be input so that managers in companies engaged in the fast fashion business must increase the perceived usefulness, perceived value, and perceived enjoyment that consumers can get when making fast fashion purchases, especially online purchases, fast fashion company managers are expected to provide information or reviews on each product sold clearly, in increasing consumer confidence, the manager of a fast fashion company must carry out several strategies so that consumer confidence continues to increase. Future research is expected to be able to examine the factors that influence purchase intention in fashion consumers, which can be investigated with other variables not examined by previous studies so that the results of this study are more developed than previous research. In addition, further research can also conduct research not only on fast fashion so that the number of samples is larger and represents the current fashion business.